AMIL ZAKAT AUTHORITY ACCORDING TO LAW OF ISLAMIC LAW AND LAW - Nurhadi Nurhadi (VALUTA, 2019)
History records the development of amil zakat in Indonesia starting from 1968 issued Regulation of the Minister of Religious Affairs No. 4 of 1968 on the Establishment of Amil Zakat and Regulation of the Minister of Religious Affairs No. 5 of 1968 on the Establishment of Baitul Maal. On 12 December 1989 issued the Instruction of the Minister of Religious Affairs 16/1989 on the Development of Zakat, Infaq and Shadaqah. In 1998-1999 and 2001-2003 formed BAZNAS of the Presidential Decree until 2011 was born a law that regulates the processing of zakat on Law no. 23 of 2011. From here the author wants to discuss what is meant by amil zakat and kopetensinya according to the Law and Islamic Law. Amil zakat is the people who are involved or actively participate in zakat activity which starts from collecting zakat from muzaki to distributing it to mustahik. According to the law in Indonesia, zakat's zakat is very important in paying zakat funds and channeling it to mustahiq, but the dominant collection should be supported by the authorities. According to Islamic law kiletensi amil zakat very urgent also, especially if amilnya fair and transparent. While the competence of the government in increasing the Baznas aggregation in collecting zakat is very urgent, especially if MUI can issue fatwas to cut the salary for civil servants / ASN to be more effective in collecting zakat and will maximize the Baznas in alleviating poverty and prospering the community